Characteristics of Two Crustins from Alvinocaris longirostris in Hydrothermal Vents - Lu-Lu Guo (MDPI AG, 2021)
Crustins are widely distributed among different crustacean groups. They are characterized by a whey acidic protein (WAP) domain, and most examined Crustins show activity against Gram-positive bacteria. This study reports two Crustins, Al-crus 3 and Al-crus 7, from hydrothermal vent shrimp, Alvinocaris longirostris. Al-crus 3 and Al-crus 7 belong to Crustin Type IIa, with a similarity of about 51% at amino acid level. Antibacterial assays showed that Al-crus 3 mainly displayed activity against Gram-positive bacteria with MIC50 values of 10–25 μM. However, Al-crus 7 not only displayed activity against Gram-positive bacteria but also against Gram-negative bacteria Imipenem-resistant Acinetobacter baumannii, in a sensitive manner. Notably, in the effective antibacterial spectrum, Methicillin-sensitive Staphylococcus aureus, Escherichia coli (ESBLs) and Imipenem-resistant A. baumannii were drug-resistant pathogens. Narrowing down the sequence to the WAP domain, Al-crusWAP 3 and Al-crusWAP 7 demonstrated antibacterial activities but were weak. Additionally, the effects on bacteria did not significantly change after they were maintained at room temperature for 48 h. This indicated that Al-crus 3 and Al-crus 7 were relatively stable and convenient for transportation. Altogether, this study reported two new Crustins with specific characteristics. In particular, Al-crus 7 inhibited Gram-negative imipenem-resistant A. baumannii.